Office ergonomics - Smith, Bo; Cuttrell, Steve; Safety Max Corporation ([Singapore] : Safety Max)
This program shows how ergonomic problems occur in office situations, which parts of the body are most susceptible, and provides practical solutions to prevent physical strain
Title from title screen
English subtitles
Executive producer, Donald L. Leonard ; editor, Anthony J. Bosco III
Keywords: Human engineering; Occupational Health; Office management